Mortality associated with periodic limb movements during sleep in amyotrophic lateral sclerosis patients - Alexander Joseph Moszczynski; Anu Tandon; Fernando Morgadinho Santos Coelho; Lorne Zinman; Brian Murray (Einstein (São Paulo))
OBJECTIVE: To describe the prevalence and severity of periodic limb movements during sleep in amyotrophic lateral sclerosis patients and to explore this fact as a predictor of severity of the condition with respect to mortality. METHODS: In this case-control study, questionnaire and polysomnographic data were analyzed from 35 amyotrophic lateral sclerosis patients. Controls were matched by age, genre, and body mass index. A Kaplan-Meier curve was used to compare the survival time of patients with periodic limb movements of sleep index below or above 5. RESULTS: The number of amyotrophic lateral sclerosis patients with an index greater than five was higher than controls (19 (53%) versus 4 (11%); p<0.0001), and the mean index was higher (23.55±40.07 versus 3.28±8.96; p=0.0009). Earlier mortality was more common in patients with more than five periodic limb movements per hour of sleep than patients with less than five periodic limb movements per hour of sleep (7/19 (37%) versus 1/16 (6%); p=0.04) in this group of patients that had a mean survival of 33 months. CONCLUSIONS: There were more periodic limb movements of sleep in amyotrophic lateral sclerosis patients than in the control population. The higher number of these movements in amyotrophic lateral sclerosis patients correlates with disease severity and may suggest poor survival.